A capital markets union without capital(ists)? - Robert Holzmann (Oesterreichische Nationalbank (OeNB), 2024)
With the capital markets union (CMU), the European Union embarked on one of its yet most ambitious and potentially most relevant reform projects. However, the huge potential for the European economy by a genuine CMU has not yet been realized. The key reason for this is that an important prerequisite for the establishment of a deep and integrated capital market is still missing, namely powerful investors. With the recent contributions of Enrico Letta (2024) and Christian Noyer (2024), there are important proposals on the table. These welcome initiatives notwithstanding, the issue of private institutional investors who can deploy very large volumes of capital in risky markets for the longer term needs to get much more attention from policymakers and financial institutions. In an aging Europe, this role could increasingly be played by European pension funds - as resource aggregators and wholesale investors - and large-scale European investment funds - as investors in innovation in Europe and beyond.
Keywords: 330; Internationaler Finanzmarkt; Marktintegration; Anlageverhalten; Pensionskasse; Investmentfonds; EU-Staaten